1993
DOI: 10.1159/000247301
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14 Monocyte Antigen in Suction Blister Fluid and Serum of Patients with Psoriasis

Abstract: The purpose of this study was to measure soluble CD 14 (sCD14) molecules in the skin and in serum of patients with psoriasis. CD 14 is a newly discovered cell surface marker on monocytes that is shed after cell activation. The following procedures were used: suction blisters were raised over the abdominal skin of 9 healthy control individuals and 8 patients with psoriasis. Serum of 17 healthy controls and 17 patients with psoriasis was collected. sCD14 was determined in suction blister fluid and serum by the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Peripheral blood precursor cells are heterogeneous, and preferential emigration of a certain subpopulation from the blood into psoriatic plaques [15,35] may well influence the preferential macrophage phenotype and its interactions in the plaques. Several studies have shown that untreated psoriatic monocytes are activated and shed more CD14 than monocytes from healthy controls [41] and secreting factors that enhance neutrophil function [31]. Monocytes from patients with psoriatic or rheumatoid arthritis are more sensitive to the actions of IL-4 than macrophages from involved joints including induction of CD23 expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood precursor cells are heterogeneous, and preferential emigration of a certain subpopulation from the blood into psoriatic plaques [15,35] may well influence the preferential macrophage phenotype and its interactions in the plaques. Several studies have shown that untreated psoriatic monocytes are activated and shed more CD14 than monocytes from healthy controls [41] and secreting factors that enhance neutrophil function [31]. Monocytes from patients with psoriatic or rheumatoid arthritis are more sensitive to the actions of IL-4 than macrophages from involved joints including induction of CD23 expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…Second, serum-dependent binding of FITC-labelled LPS to a combined mutant, CD14 (9-13/57, 59, 61-63)A is hardly detectable [80]. Determination of the Kd value reveals that the combined mutant has a fourfold higher Kd (124 nM) than measured for CD14 (9)(10)(11)(12)(13)A , and CD14 (57,59,(61)(62)(63)A . Together, both regions 9-13 and 57-64 might contribute to a three-dimensional structure which forms the LPS-binding groove of human CD14.…”
Section: Identification Of the Lps-binding Site Of Human Cd14mentioning
confidence: 87%
“…These situations include chronic inflammatory diseases such as psoriasis [62], sarcoidosis [63] and systemic lupus erythematosus [64] and chronic infections such as HIV infection [65,66]. The molecule has also been in focus as a putative surrogate marker for the monitoring of intensive care patients: Krü ger et al [67] detected elevated sCD14-serum levels in patients suffering from polytrauma and burns and Endo et al [68] found higher sCD14 levels in septic patients with multi-organ failure.…”
Section: Generation Of Soluble Cd14 and Soluble Cd14 Isoformsmentioning
confidence: 99%
“…Martin et al [23] detected markedly increased sCD14 levels in serum and bronchoalveolar lavage fluid of patients with acute respiratory distress syndrome. Furthermore, elevated sCD14 levels have been reported in patients with psoriasis [24] and systemic lupus erythematosus [25]. To date it is unclear whether the increase of sCD14 is a phenomenon crucial to the pathogenesis of disease or a mere epiphenomenon caused by activation of inflammatory cells.…”
Section: Monocyte Lps Receptor Cd14mentioning
confidence: 99%
“…Further reports indicated that this pathway is also used by vascular smooth muscle cells [35], and CD14-negative monocytes derived from patients suffering from paroxysmal nocturnal haemoglobinuria [36][37][38]. The human CD14 cDNA was cloned in 1988 by Ferrero and Goyert [39,40], and the gene has been localised on chromo-some 5 (5q [23][24][25][26][27][28][29][30][31]. The mature 53 kDA protein consists of 356 amino acids and shows homology only to an inducible Gramnegative bacteria-binding protein from the silkworm [41].…”
Section: Monocyte Lps Receptor Cd14mentioning
confidence: 99%